MENJADI REMAJA SEJATI DALAM KRISTUS EDUKASI DAN PEMBINAAN KARAKTER DI DESA BAWOZA’UA - Gaurifa, Timahati (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program "Becoming True Teenagers in Christ" aims to build the spiritual character of teenagers in the village of Bawoza’ua through various activities, including spiritual leadership training, spiritual retreats, the development of digital learning modules, and program evaluation. This program focuses on strengthening Christian values, spiritual development, and social concern among teenagers. The evaluation is conducted using a qualitative approach through group discussions and in-depth interviews with teenagers, parents, pastors, and religious teachers. A quantitative approach uses questionnaires to measure changes in attitudes and understanding of Christian values among teenagers. The evaluation results show a positive impact on the improvement of spiritual character and social behavior among teenagers, as well as the success of the program in introducing digital-based learning relevant to the needs of today's youth. The sustainability of the program heavily depends on the active role of the community and parents in supporting the spiritual growth of the teenagers.